Skala zewnętrznych ograniczeń w kredytowaniu agrobiznesu (na przykładzie województwa mazowieckiego) - Gajowiak, Dominik (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2005)
The study presents external limitations in crediting of agribusiness in Masovia Province. The scope of them was presented on the example of the most popular four preferential credit lines in the years from 2000 to 2002. In this period the credits for young farmers and for purchases of lands had the lowest scope of external limitations, but the rest of credit lines was characterized by the highest scope of limitations. Main reasons for external limitations of crediting agribusiness are transaction costs and volume of deposits in banks. External limitations depend on other barriers which are less or more consciously created by formal financial institutions.